Association of Genetic, Environmental, and Nutritional Factors With Metabolic Phenotypes of Obesity: A Scoping Review - Haniyeh Danesh Doost; Milad Nasiri Jounaghani; Roya Riahi; Motahar Heidari-Beni; Mohsen Hosseini; Fariborz Sharifianjazi; Roya Kelishadi (Journal of Obesity)
Conclusion: Environmental and nutritional factors can increase metabolic abnormalities. Metabolic phenotype categories are useful for predicting disease risk and for developing personalized diets and environmental interventions. These findings may help develop strategies to improve metabolic health.